Analyzing “Kubah” and Efforts to Reconcile the 1965 Tragedy - Muh. Fatoni Rohman (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Social conflict is a certainty for multiethnic societies such as Indonesia. As such efforts to prevent and seek a resolution to conflicts are an absolute matter. Writers through their works may actively contribute by creating works that contain values and attitudes of peace. The novel Kubah by Ahmad Tohari is one of the works that discuss the reconciliation of the 1965 tragedy. This novel explains the stages of reconciliation that both offenders and victims may go through. These stages are revealing the truth, forgiveness, and healing.